Initial professional development for civil engineers - Steels, H. Macdonald (ICE, 2011)
Providing guidance for all candidates and their mentors to make sense of the IPD process, this text gives valuable insight into how to review their experience and the learning they must take from it. The book offers every review candidate the vision to select the key, important elements of experience to demonstrate their understanding, skills, knowledge and insight.